(untitled) (Jurnal EurekaMatika, 2016)
This paper tells about dilation theory with a Hilbert space as an underlying space and associations between some of dilation theory consist of completely positive maps, contraction and operator-valued measure. In addition also tells about dilation theory with a Banach space as an underlying space. ABSTRAK Pada artikel ini dibahas teori dilasi dengan ruang Hilbert sebagai ruang pokok dan kaitan antara beberapa teori dilasi yang terdiri dari pemetaan positif lengkap, kontraksi dan ukuran bernilai operator. Selain itu dibahas juga teori dilasi dengan ruang Hilbert sebagai ruang pokok.